2014
DOI: 10.1063/1.4870802
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic degradation of thin film multilayers during ion milling

Abstract: We present a study of Ar ion milling-induced damage in exchange biased IrMn/CoFe/Ag-based magnetic multilayer thin films. While process variations determine the change in CoFe magnetic properties, the distance from the ion milling front to the IrMn/CoFe interface dominates the extent of exchange bias damage. Remarkably, the interfacial coupling energy Jk can be reduced by 50% before any removal of the CoFe pinned layer. We attribute the losses to microstructural changes and damage effects where cap material is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, as can be seen from the data the dissociation and the final level of order are very different. This could be due to the M S values used from the thin film data actually being different to that of the final island material as it has been shown that ion beam milling can affect the magnetic properties of some materials and effectively lower their magnetization [27][28][29] . This highlights the importance of experimental and material considerations for potential device applications where one might want to manipulate the direction of motion of these emergent magnetic charges.…”
Section: Discussionmentioning
confidence: 99%
“…However, as can be seen from the data the dissociation and the final level of order are very different. This could be due to the M S values used from the thin film data actually being different to that of the final island material as it has been shown that ion beam milling can affect the magnetic properties of some materials and effectively lower their magnetization [27][28][29] . This highlights the importance of experimental and material considerations for potential device applications where one might want to manipulate the direction of motion of these emergent magnetic charges.…”
Section: Discussionmentioning
confidence: 99%
“…This work uses the nanodisc fabrication method outlined in a previous study 25 : nanosphere lithography is used to create a mask across the surface of a thin film, which is then ion milled to "cut out" disc shaped particles (see Section S2 in the supplementary material for more detail). The ion milling step utilises accelerated Ar ions to bombard the film, which has been shown to cause significant modification of magnetic multilayer properties 28 . Firstly, a rise in temperature during milling can disrupt the interfaces through atomic diffusion [29][30][31][32] .…”
mentioning
confidence: 99%
“…Firstly, a rise in temperature during milling can disrupt the interfaces through atomic diffusion [29][30][31][32] . Secondly, the bombarding ions can create defects in multiple ways 28,33,34 : Ar ion implantation, sputtering away of stack atoms or mixing of stack atoms. If the induced defects are on the length scale that is associated with domain wall dynamics 35 , this could alter domain nucleation or pinning behaviour.…”
mentioning
confidence: 99%
“…Patterning was accomplished using photolithography, followed by argon ion milling at a base pressure of 3×10 -8 Torr, with ion energy of 300V and a beam current of 100mA for 4 minutes. Ion milling is known to result in deep pinning sites and these are randomly distributed along the stripes [31].…”
mentioning
confidence: 99%